2001
DOI: 10.1128/iai.69.12.7946-7949.2001
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Overlapping Epitopes in the Repetitive Unit of the Shed Acute-Phase Antigen from Trypanosoma cruzi Enhance Its Immunogenic Properties

Abstract: The repetitive shed acute-phase antigen (SAPA) from Trypanosoma cruzi was thoroughly mapped by SPOT peptides and phage display strategies, showing that a single SAPA repeat is composed of multiple overlapping B-cell epitopes. We propose that this intricate antigenic structure constitutes an alternative device to repetitiveness in order to improve its immunogenicity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
37
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(40 citation statements)
references
References 22 publications
(15 reference statements)
2
37
0
Order By: Relevance
“…Moreover, ϳ80% of the reactive serum samples (36/46) showed similar antibody titers toward either molecule (i.e., ⌬ absorbance values, Ͻ25%; data not shown). TSSA-CL [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and TSSA-CL 48-62 , on the other hand, yielded negative results for every serum sample tested (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, ϳ80% of the reactive serum samples (36/46) showed similar antibody titers toward either molecule (i.e., ⌬ absorbance values, Ͻ25%; data not shown). TSSA-CL [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] and TSSA-CL 48-62 , on the other hand, yielded negative results for every serum sample tested (Fig. 1C).…”
Section: Resultsmentioning
confidence: 99%
“…TSSA-CL [48][49][50][51][52][53][54][55][56][57][58][59][60][61][62] matched the sequence of p48-62 in the chip array, which was also recorded as negative for both IgG samples (see Table S3 in the supplemental material). In the case of TSSA-CL [24][25][26][27][28][29][30][31][32][33][34][35][36][37][38] , however, its matching peptide (p24-38) was recorded as positive for both IgG samples in our chip assay (see Table S3). Despite this discrepancy, which can be attributed to a higher sensitivity of the microarray, our data showed a close agreement between the two kinds of assays (peptide-chip arrays and GST-fusion protein-based ELISA).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We describe the use of a random peptide phage display library to identify immunogenic proteins from P. aeruginosa. The use of phage display for the identification of immunogenic proteins has been demonstrated to be useful for development of vaccines against human diseases such as cancer (17,38,39) and many diverse human pathogens, including Neisseria meningitides (28,22,27), Echinococcus granulosus (21), and Trypanosoma cruzi (2). However, the use of a random peptide phage display library rather than a recombinant library made with DNA from the pathogen of interest is a novel technique that has been used in N. meningitidis to identify mimotopes of nonpeptide antigens (28).…”
Section: Discussionmentioning
confidence: 99%
“…Natural humoral responses to many T. cruzi antigens appear to be directed to epitopes encoded by these repeat units. It has been suggested that the immune response to parasite repetitive antigens does not protect the host because it masks the host's immune response to more critical epitopes on different molecules (1,2,6,10,14).…”
mentioning
confidence: 99%